INDEKS KESEHATAN GIGI SISWA TAMAN KANAK-KANAK DI KELURAHAN MERGOSONO, MALANG - Rahmavidyanti Priyanto; Yuliana Ratna Kumala; Yuli Nugraeni; Ria Puspita Sari; Sherli Puspa Adini; Marsha Seruni Agam (JURNAL PENGABDIAN MASYARAKAT KESEHATAN (ABDIMAKES), 2024)
Dental and oral health, especially for children, is often considered a trivial matter. In fact, a healthy oral cavity condition at an early age will support the health of the oral cavity as an adult. The high rate of tooth decay in children should be a concern for parents, teachers and medical personnel. When complex dental and oral abnormalities occur in children, medical treatment causes trauma to their psychological condition, so it is much easier to prevent tooth decay through efforts to improve dental and oral health from an early age. Based on the results of dental and oral screening conducted on kindergarten children in Mergosono, Malang, it was found that the def-t score in children aged 4 years old is in the criteria of high (4,5), 5 years old is very high (7,7) and 6 years old is very high (6,8). The cause of the high incidence of dental caries in kindergarten children is the lack of knowledge about oral health, which can be concluded from the wrong behavior or way of brushing their teeth and the right knowledge about when to brush their teeth. Efforts that can be made to improve this behavior are education which is included in promotive and preventive efforts.